MAKNA LEKSIKAL DAN MAKNA GRAMATIKAL DALAM BAHASA ARAB - Alfan Aulawi; Akmaliyah (MUHIBBUL ARABIYAH: Jurnal Pendidikan Bahasa Arab, 2025)
Understanding lexical and grammatical meaning in Arabic is essential for linguistic studies and language learning. This study aims to explore the concept of lexical meaning, such as synonyms, antonyms, homonyms, hyponyms, and hypernyms, as well as grammatical meaning that emerges from the structural context of words and sentences in Arabic. Using a literature study method, this study analyzes relevant literature, including books, journal articles, and other scientific works, to reveal the interaction and importance of the two types of meaning. A qualitative descriptive approach is used to identify patterns and relationships in the data. The results show different roles between lexical meaning, which forms the basis of vocabulary, and grammatical meaning, which enables the construction and interpretation of sentences accurately. These two types of meaning are interrelated and contribute significantly to the richness of the Arabic language.